Reduced Retinoic Acid Signaling During Gastrulation Induces Developmental Microcephaly - Gur, Michal; Bendelac-Kapon, Liat; Shabtai, Yehuda; Pillemer, Graciela; Fainsod, Abraham (Frontiers in Cell and Developmental Biology, 2022)
Retinoic acid (RA) is a central signaling molecule regulating multiple developmental decisions during embryogenesis. Excess RA induces head malformations, primarily by expansion of posterior brain structures at the expense of anterior head regions, i.e., hindbrain expansion. Despite this extensively studied RA teratogenic effect, a number of syndromes exhibiting microcephaly, such as DiGeorge, Vitamin A Deficiency, Fetal Alcohol Syndrome, and others, have been attributed to reduced RA signaling. This causative link suggests a requirement for RA signaling during normal head development in all these syndromes. To characterize this novel RA function, we studied the involvement of RA in the early events leading to head formation in Xenopus embryos. This effect was mapped to the earliest RA biosynthesis in the embryo within the gastrula Spemann-Mangold organizer. Head malformations were observed when reduced RA signaling was induced in the endogenous Spemann-Mangold organizer and in the ectopic organizer of twinned embryos. Two embryonic retinaldehyde dehydrogenases, ALDH1A2 (RALDH2) and ALDH1A3 (RALDH3) are initially expressed in the organizer and subsequently mark the trunk and the migrating leading edge mesendoderm, respectively. Gene-specific knockdowns and CRISPR/Cas9 targeting show that RALDH3 is a key enzyme involved in RA production required for head formation. These observations indicate that in addition to the teratogenic effect of excess RA on head development, RA signaling also has a positive and required regulatory role in the early formation of the head during gastrula stages. These results identify a novel RA activity that concurs with its proposed reduction in syndromes exhibiting microcephaly.